2022
DOI: 10.3390/nu14224852
|View full text |Cite
|
Sign up to set email alerts
|

Meat Intake, Cooking Methods, Doneness Preferences and Risk of Gastric Adenocarcinoma in the MCC-Spain Study

Abstract: Background: The association of meat intake with gastric adenocarcinoma is controversial. We examined the relation between white, red, and processed meat intake and gastric adenocarcinoma, considering doneness preference and cooking methods, by histological subtype and anatomical subsite. Methods: MCC-Spain is a multicase–control study that included 286 incident gastric adenocarcinoma cases and 2993 controls who answered a food-frequency questionnaire. The association of gastric adenocarcinoma with meat intake,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The prevalence of H. pylori infection has been estimated at around 50% in Argentina and Mexico, and over 70% in Brazil and Chile ( Hooi et al ., 2017 ). Established risk factors beyond H. pylori include nonmodifiable exposures, such as male sex, family history of gastric cancer, carrying some genetic variants, or even living in high-altitude countries, which is probably a surrogate for host genetic, bacterial, dietary, and environmental factors that may cluster in the mountainous regions ( Torres et al ., 2013 ; Boldo et al ., 2022 ), but also lifestyle factors such as tobacco smoking, alcohol use, high consumption of red and processed beef ( Nikitina et al ., 2023 ) meat, and high-sodium diet ( Bonequi et al ., 2013 ; Praud et al ., 2018 ; Arnold et al ., 2020 ; Deng et al ., 2021 ; Boldo et al ., 2022 ). In addition, populations in mountainous areas tend to be of lower socioeconomic status, which is a recognized determinant risk for gastric cancer ( Rota et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of H. pylori infection has been estimated at around 50% in Argentina and Mexico, and over 70% in Brazil and Chile ( Hooi et al ., 2017 ). Established risk factors beyond H. pylori include nonmodifiable exposures, such as male sex, family history of gastric cancer, carrying some genetic variants, or even living in high-altitude countries, which is probably a surrogate for host genetic, bacterial, dietary, and environmental factors that may cluster in the mountainous regions ( Torres et al ., 2013 ; Boldo et al ., 2022 ), but also lifestyle factors such as tobacco smoking, alcohol use, high consumption of red and processed beef ( Nikitina et al ., 2023 ) meat, and high-sodium diet ( Bonequi et al ., 2013 ; Praud et al ., 2018 ; Arnold et al ., 2020 ; Deng et al ., 2021 ; Boldo et al ., 2022 ). In addition, populations in mountainous areas tend to be of lower socioeconomic status, which is a recognized determinant risk for gastric cancer ( Rota et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although cancer is classified as a diet-related disease, the influence of diet on the development of oral cancer has so far been poorly understood [5,32,33]. The frequent consumption of certain products, including red meat and its products, is a risk factor for the development of gastrointestinal cancer [34][35][36].…”
Section: Consumption Of Meat and Meat Products As Risk Factors In The...mentioning
confidence: 99%
“…The majority of studies show a significant association between red meat consumption and the development of gastric cancer. Some studies have found that red meat consumption is linked to an increased risk of gastric cancer [5,19,20,23,26,27,[44][45][46][47][48]. For example, Kim et al found that both red and processed meat consumption were associated with a higher risk of gastric cancer, and Song et al found that the highest level of red meat intake was associated with a 37% increased risk of gastric cancer [5,19].…”
Section: Gastric Cancermentioning
confidence: 99%